2009
DOI: 10.1038/jcbfm.2009.220
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol, a Phosphodiesterase Inhibitor, Attenuates Photothrombotic Focal Ischemic Brain Injury in Hypertensive Rats

Abstract: The aim of this study was to evaluate and compare the effects of anti-platelet agents with different modes of action (cilostazol, aspirin, and clopidogrel) on brain infarction produced by photothrombotic middle-cerebral-artery (MCA) occlusion in male, spontaneously hypertensive rats. Cerebral blood flow (CBF) was measured with laser-Doppler flowmetry in the penumbral cortex. Infarct size was evaluated 24 h after MCA occlusion. The effects of these drugs on infarct size were examined by pretreatment of rats und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 37 publications
2
32
0
Order By: Relevance
“…This protective effect of cilostazol is in accordance with the previous findings that cilostazol improved cerebral infarction by reducing cytotoxic edema in rats (Lee et al 2003;Ito et al 2010;Wajima et al 2011). Cilostazol also reversed the reduction of claudin-5 expression and normalized the increase of MMP-9 activity to prevent tissue plasminogen activator (tPA)-associated hemorrhagic transformation induced by focal cerebral ischemia in mice treated with tPA (Ishiguro et al 2010).…”
Section: Effect Of Cilostazol On Barrier Function Of Rbec Damaged By supporting
confidence: 78%
“…This protective effect of cilostazol is in accordance with the previous findings that cilostazol improved cerebral infarction by reducing cytotoxic edema in rats (Lee et al 2003;Ito et al 2010;Wajima et al 2011). Cilostazol also reversed the reduction of claudin-5 expression and normalized the increase of MMP-9 activity to prevent tissue plasminogen activator (tPA)-associated hemorrhagic transformation induced by focal cerebral ischemia in mice treated with tPA (Ishiguro et al 2010).…”
Section: Effect Of Cilostazol On Barrier Function Of Rbec Damaged By supporting
confidence: 78%
“…17 Previous studies have shown that cilostazol increases rCBF in a rat model of chronic cerebral hypoperfusion, 18,19 and that cilostazol improves rCBF in the penumbral region in a rat model of middle cerebral artery occlusion. 20 In clinical studies, cilostazol also increases rCBF compared with ticlopidine at the chronic stage of cerebral infarction with a vasodilating effect. 21 In the present study, cilostazol tended to maintain rCBF compared with vehicle and the other 2 antiplatelet drugs (Figure 1).…”
Section: Omote Et Al Pleiotropic Effect Of Cilostazol In Shr-spmentioning
confidence: 99%
“…11,12 Several studies showed that short-term pretreatment and post-treatment with cilostazol attenuated ischemic brain injury by increasing NO production and eNOS activation. [13][14][15] However, the comparative effects of cilostazol and aspirin on cerebrovascular function have not been investigated.We hypothesized that chronic cilostazol treatment, in contrast to aspirin treatment, (1) can prevent hypertensioninduced cerebrovascular dysfunction through increased eNOS-Ser 1177 phosphorylation and the eNOS-dependent CBF …”
mentioning
confidence: 99%